Nacre-like ceramics and composites - Ma, Zhuoran (Nanyang Technological University, 2022)
Nowadays, it is pressing to develop novel high-performance structural materials to satisfy various applications, such as aircraft’s engines, artificial teeth and bones. The natural abalone shells have the characteristics of being light weight and exhibit excellent mechanical properties, which provide a basis for the material design. A previous fabrication method called vacuum assisted magnetic alignment (VAMA) was designed to optimize nacre-like materials fabricating methods by reducing the fabrication time and enhancing the material density. Here, a series of nacre-like alumina (NLA) ceramics was prepared by VAMA and the effect of processing parameters on the microstructure and flexural strength were explored. Under the influence of pressure drop and drying time, 3 mm was verified as the most reliable forming thickness to achieve high flexural strength and density. The relative density and flexural strength also increased as the drop of filter pressure, especially from 1.2×10-2 MPa to 0.7×10-2 MPa. The vacuum chamber pressure of 0.7×10-2 MPa was the critical condition to offer enough suction force eliminating pores and achieving a dense structure with uniform micro-platelets alignment. Moreover, a double-layered NLA ceramic was designed. Each layer was distinguished by different micro-platelets aspect ratio and an integral gradient structure with higher bulk density was obtained. The extensive crack deflection increased the energy release and improved the flexural strength by 15%, which was over 200 MPa. The structure also showed a potential ability to resist crack propagation and achieving a high fracture toughness.